The Effectiveness of the Problem Based Learning (PBL) Model in Increasing Students’ Learning Interest through Quizizz Media on Procedure Text Material at MAN 1 Pamekasan. - Fitriyah, Fitriyah; Yulianti, Sri Ratih; Hidayah, Linta Wafdan; Afrianti, Tri Dessy (The Ellite of Unira, 2025)
AbstractThis study investigates the effectiveness of the Problem Based Learning (PBL) model combined with Quizizz media in enhancing students’ interest and learning outcomes in English procedure text material at MAN 1 Pamekasan. The motivation for this research stems from preliminary observations indicating students’ low enthusiasm in English classes due to monotonous learning methods and media. The study applies Classroom Action Research (CAR) with two cycles, each consisting of planning, acting, observing, and reflecting stages. Participants of the study were 11th-grade students in class XI E. Data were collected through observation and tests, with results evaluated using pre-test and post-test comparisons. The findings show a significant improvement in students’ engagement and academic performance. In cycle I, the average score increased from 45 to 60, and in cycle 2, from 65 to 80. Additionally, student participation during class activities improved, particularly in listening, group discussion, and task completion. The integration of PBL and Quizizz created a more interactive and enjoyable learning environment, encouraging students to be more active and motivated. Thus, this method is proven to be an effective and innovative strategy to enhance students’ interest and achievement in learning English, especially in understanding procedure texts. The study provides a valuable insight into contextual learning innovation in the Madrasah Aliyah environment. Keywords: Problem-Based Learning, Quizizz, Learning Interest, Procedure Text, English Language Teaching